2017
DOI: 10.1002/jcb.26226
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Biomarkers for Early Diagnosis of Acute Myocardial Infarction

Abstract: Acute myocardial infarction (AMI) is a common disease with serious consequences in mortality and cost. Here we aim to screen the differentially expressed genes (DEGs) as biomarkers for early diagnosis of AMI. The microarray data of AMI was downloaded from Gene Expression Omnibus (GEO), including two independent types of research GSE66360 and GSE62646. The DEGs between control and processed samples were screened out by using limma package. Meanwhile, we performed functional analysis of GO terms and/or KEGG path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…According to database prediction, miR-411-5p may be a target that binds to SOCS3 and ICAM1. These two genes have been confirmed to be associated with myocardial infarction [41,42].…”
Section: Discussionmentioning
confidence: 91%
“…According to database prediction, miR-411-5p may be a target that binds to SOCS3 and ICAM1. These two genes have been confirmed to be associated with myocardial infarction [41,42].…”
Section: Discussionmentioning
confidence: 91%
“…Studies in the past few decades have identified biomarkers that have the potential to revolutionize medical science in terms of diagnosis, prognosis, and therapy (Chowdhury et al, 2013; Selleck et al, 2017; Cesano and Warren, 2018). Biomarkers have been identified for various diseases and disorders; for example, metabolic disorders (Boenzi and Diodato, 2018), cardiovascular disease (Ho et al, 2018), myocardial infarctions (Ge et al, 2018), gynecological diseases (Flores et al, 2018; Liu et al, 2018), neurological disorders (Lashley et al, 2018) and hepatic diseases (Wallace et al, 2016; Raghu et al, 2018). In the present era of high cancer prevalence, sensitive neoplastic biomarkers are a significant research focus, which could aid the early detection and prognosis of neoplastic changes (Tainsky, 2009; Admoni-Elisha et al, 2016; Andersen et al, 2017; Liu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Then, the DMSs were mapped to genes, that is, differentially methylated genes (DMGs), according to the platform annotation file. The differentially expressed genes (DEGs) were identified through Limma package in R Bioconductor, with |log2 (fold change)| > 1 and P < 0.05 indicating significance . Since methylation may negatively influence gene expression, we performed a cross‐analysis of DMGs and DEGs.…”
Section: Methodsmentioning
confidence: 99%